FutureGen – Predicting Genetic Health - Omkar Sanjay Kamble; Soham anand borage; Tanay Prabhakar Pandit; Shaikh Mohammed Zaid Manzoor; Bhavesh santosh katkar; Rama Bansode (International Journal of Genetic Modifications and Recombinations, 2026)
FutureGen is an intelligent web-based system developed to help couples assess the risk of genetic disorders in their future child through data-driven analysis. The system brings together modern web technologies and machine learning to offer accurate and accessible predictions. The frontend, built with React, provides an intuitive interface for user interaction, while a Flask-based backend API handles model inference and manages communication with the Supabase database, which securely stores user and prediction data. The machine learning engine, powered by a Random Forest classifier, processes clinical and parental information such as age, carrier status, and family medical history to estimate the likelihood of hereditary disorders. By integrating AI with healthcare insights, FutureGen aims to promote early awareness, support genetic counseling, and assist couples in making informed family planning decisions.
Keywords: AI in Healthcare; Genetic Disorder Prediction; Genetic Risk Assessment; Parental Health Data; machine learning